Open-Switch Fault Detection for Hybrid ANPC Inverter Based on Current Distortion - Kim, Sang Hun; Kim, Seok Min; Lee, Kyo Beum (2019 IEEE Student Conference on Electric Machines and Systems, SCEMS 2019, 2019)
In this paper, an open-switch fault detection method is proposed for a hybrid active neutral-point clamped (ANPC) inverter. The hybrid ANPC topology used 4 silicon switches and 2 silicon carbide switches to generate the three-level output voltage. The open-switch fault in the hybrid ANPC inverter leads to a distortion of the output current. The current distortion decreases efficiency and eventually breaks down the system. Therefore, an open-switch fault detection method is required to improve the reliability of the hybrid ANPC inverter. Radius and angle in the dq-axis determine the location of the faulty switch. This method identifies the faulty switch without using additional sensors. Simulation results verified the validity of the proposed method.
Keywords: Active neutral point clamped; Current distortion; Detection methods; Faulty switches; Neutral point clamped; Output voltages; Silicon carbides (SiC); Switch faults; active neutralpoint clamped (ANPC) inverter; fault detection; open-switch fault; silicon carbide (SiC)